Sequencing Batch Reactor (SBR) Technology for Biological Treatment of Sewage - Lim, Chin Ming (2001)
The sequencing batch reactor (SBR) has become popular in recent years since Irvine and Davis (1979) described its operation. The SBR achieves the processes in a framework of space compared to the conventional system, which achieves in terms of space. There are generally 5 operational steps in a SBR cycle namely Fill, React, Settle, Draw and Idle. A bench scale SBR was studied at 2 different strategies. The study was conducted at different cycle times (6h, 8h and lOh) and different operational mode based on the ratio of anaerobic and aerobic period (1/2.7, 1/1 and l.7/l). The study was undertaken to investigate the effluent quality, removal efficiency, SVI and kinetic growth coefficient. Results from strategy A (different cycle time) showed that increases in cycle time led to decrease in the removal of TSS, COD and BODs. Best results were obtained for the system with the 6h-cycle time, followed by the 8h-cycle time and lastly was the 10h-cycle time. Six hours cycle time was chosen for strategy B mainly due to the overall better removal efficiency on TSS, COD and BODs. There were 3 operational modes being examined in strategy B, they were 112.7 (longest aerobic period), 1/1 and 1.7/1(shortest aerobic periods). Best results were obtained from the 1/2. 7 operational mode with the longest aerobic period (lowest Li, which was 1. 22 mg/mg.d), followed by 1/1 operational mode and lastly was the 1.711 operational mode. The higher removal efficiency was associated with the longer aerobic period, the kinetic growth coefficient and SVI also increased with the increasing of aerobic period. Therefore, the 6h-cycle time and 112.7 operational mode appeared to be the most reliable option in this study. F or further studies, more work could be done to have a better understanding of the SBR system. For instance, inclusion of an anoxic period in the React step would enhance denitrification process to achieve better effluent quality. Moreover, kinetic growth model can be further explored by thymidine assay.